2007
DOI: 10.1183/09031936.00109407
|View full text |Cite
|
Sign up to set email alerts
|

Neoalveolarisation contributes to compensatory lung growth following pneumonectomy in mice

Abstract: Regeneration of the gas exchange area by induction of neoalveolarisation would greatly improve therapeutic options in destructive pulmonary diseases. Unilateral pneumonectomy is an established model to remove defined portions of gas exchange area and study mechanisms of compensatory lung growth. The question of whether new alveoli are added to the residual lung after pneumonectomy in mice was addressed.Left-sided pneumonectomy was performed in 11 adult C57BL/6 mice. Alveolar numbers were analysed in lungs fixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
74
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(81 citation statements)
references
References 42 publications
7
74
0
Order By: Relevance
“…Sampling of lung tissue was conducted by use of tissue fractionator after embedding in 4% (wt/vol) Agar. Alveolar numbers were estimated by counting alveolar rings in serial sections using the values of parenchymal volumes calculated by point counting, as described previously (52,53).…”
Section: Methodsmentioning
confidence: 99%
“…Sampling of lung tissue was conducted by use of tissue fractionator after embedding in 4% (wt/vol) Agar. Alveolar numbers were estimated by counting alveolar rings in serial sections using the values of parenchymal volumes calculated by point counting, as described previously (52,53).…”
Section: Methodsmentioning
confidence: 99%
“…If the entire left lobe of a mouse lung is removed, total lung volume is restored within 3 weeks by compensatory growth of the right lung. Detailed stereological analysis has shown that this compensatory growth involves both expansion of remaining alveoli and the formation of new alveolar units (neoalveolarization; Voswinckel et al, 2004;Fehrenbach et al, 2008). In contrast, many chronic injuries are not repairable and can lead to lung conditions, such as emphysema in which alveolar units are lost.…”
Section: Introductionmentioning
confidence: 99%
“…All animals generate enough surface area to assure a normal life, even under physical stress [4]. One group demonstrated a regeneration of ,50% of the excised alveoli in the residual lung 20 days after unilateral pneumonectomy of mice [5]. Reporting a model of lung tissue regression and regeneration, MASSARO et al [6] showed the ability of mice to fully regrow alveolar surface area that was diminished during calorie restriction, again showing an inherent regenerative potential also under different circumstances.…”
mentioning
confidence: 99%